Capabilities of Disaster Resilent Villages in Mitigation of Lanside Disasters Sirongge Village, Pandanarum Distrct, Banjarnegara Regency In 2020 - Yoga Adit Budi Pratama; Sakir Sakir (Universitas Muhammadiyah Ponorogo, 2023)
This study aims to determine the extent to which disaster-resilient villages are capable of mitigating landslides based on Disaster Resilient Villages in Sirongge Village, Pandanarum District, Banjarnegara Regency, to mitigate landslides in the form of landslides. By using qualitative methods through interviews with four informants, namely the head of BPBD prevention in Banjarnegara Regency, the head of Sirongge Village, the Sirongge Village government and the Sirongge Disaster Resilient Village administrator, this research was carried out for one year, researchers found that landslide disaster mitigation activities in Sirongge Village were running well in 2020, especially in non-structural mitigation, these activities are carried out in collaboration between the village government, Disaster Resilient Village volunteers, and the community through coordination from the Banjarnegara Regency BPBD, the community also plays an active role in carrying out mutual activities. cooperation, because it is through the disaster-resilient village program, Sirongge Village is able to face and reduce the risk of landslides, the suggestions in this study include, The village government continues to look for new innovations as a means of mitigating landslides in Sirongge Village, the community needs to develop raise awareness of the Disaster Resilient Village program In Sirongge Village, the village government provides information boards in the form of posters on landslide disaster mitigation procedures